Research of technology of cultivation and collection of medicinal plants - Stroyanovskyy , V. S.; Padalko, T. O.; Kozina, T. V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
As a result of the performed researches the expediency of growing chamomile plants in natural and climatic conditions of the Right-Bank Forest-Steppe of Ukraine is substantiated. Varieties in terms of stability and biological characteristics are an important indicator in the emergence of simultaneous shoots, the formation of the number and weight of shoots, leaves and inflorescences, which is an indicator of increasing the yield of raw materials. Biometric analysis proved that the studied factors influenced the structure of plants. The Perlyna Lisostepu variety was more productive than the Bodegold variety. Thus, the maximum size was reached by plants formed in the most favorable conditions against other years of research, in 2019, when plants of the Perlyna Lisostepu variety, on variants for autumn sowing with seeding rate of 6 kg / ha, reached 71.2 cm in height for 16.0 pieces of inflorescences on one plant at weight of inflorescences of 7 g from a plant, quantity of shoots – 18.2 pieces and leaves – 84.7. The minimum indicators were observed in 2017 of the Bodegold variety at a seeding rate of 8 kg / ha during the summer sowing period. According to our calculations, they were: plant height - 40.5 cm; number of shoots - 4.0; leaves - 68.5; inflorescences - 3.7 weighing 1.5 g from one plant. On average, with an increase in plant height by 13.4%, the number of shoots was 25.8%, and the number of inflorescences per plant - 23.4%, which led to an increase in the weight of inflorescences per plant by 14.4% and the weight of 1000 seeds up to 6.7% with clean sowing and without the introduction of chemicals.